The Different Types of Words Meaning in Minangkabau Proverbs: A Stylistics Approach - Syamsul Bahri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The objective of this study is to find out the description of several different types of words meaning in Minangkabau Proverbs based on a stylistic approach. This research uses descriptive qualitative method in which the description and   interpretation on the real fact or object of the research done by using Minangkabau proverbs recorded  from about 8 respondents of Minangkabau Natives. The library study is also done to find several sources focused on stylistic devices based on different types of word meaning in Minangkabau proverbs. This research uses the theory from (Lethsalu, Liiv, & Mut, 1973). There are two types of stylistic devices, the first types of stylistic devices based on the interaction of lexical and contextual meaning consist of metaphor, metonymy, antonomasia, and irony.The second types of stylistic devices based on different types of word meaning consist of epithet, oxymoron, hyperbole, and meiosis. The findings show that there are several types of word meaning in Minangkabau Proverbs, namely Metaphor 68%, Metonymy 6%, Irony 8%, Epithet 2%, Hyperbole 6%, and Zeugma 10%. The dominant types of word meaning in Minangkabau Proverbs is Metaphor. It shows that  people in Minangkabau always use decorated language that uses nature as its object, to show the nature, characteristics or condition of something. Minangkabau people learn about life from nature, the process of something become something better.